Functional Outcome of Pediatric Monteggia Fracture Dislocation Treated Surgically in a Tertiary Care Centre of Nepal - Dhoju, D.; Parajuli, B. (Kathmandu University Medical Journal, 2021)
Background Monteggia fracture dislocation may need operative management. The fracture of ulna is reduced by closed or open reduction followed by stabilization of ulna with Rush pin, K-wires or Dynamic compression plate. Objective To evaluate the Mayo Elbow Performance Score of patients with Monteggia fracture dislocation treated operatively. Method It is a retrospective study conducted at Dhulikhel Hospital, Kathmandu University Hospital. All the pediatric patients with Monteggia fracture dislocation managed operatively from January 2011- December 2019 were included in the study. The functional outcome scoring of the effected elbow using Mayo Elbow Performance Score was done in the last follow up. Result Forty eight surgically managed Monteggia patients had a mean age of 7.23 ± 2.9 years with male predominance. Left side was the dominant side of involvement with 29 patients. Bado type 1 was the most common type (81.3%). Most of the patient underwent closed reduction and fixation with Rush pin (n=40). All of the patient has excellent (89.6%) to good (10.4%) functional outcome. Conclusion Operative management of Monteggia fracture dislocation with complete ulna fracture has excellent to good outcome.